Wear particles promote endotoxin tolerance in macrophages by inducing interleukin‐1 receptor‐associated kinase‐M expression1. Issue 3 (31st August 2012) - Zhang, Yangchun; Yu, Shiming; Xiao, Jianhong; Hou, Changhe; Li, Ziqing; Zhang, Ziji; Zhai, Qiyi; Lehto, Matti; Konttinen, Yrjö T.; Sheng, Puyi
Abstract: Toll‐like receptors (TLRs) recognizing pathogen‐associated molecular patterns (PAMP) play a role in local immunity and participate in implant‐associated loosening. TLRs‐mediated signaling is regulated by interleukin‐1 receptor‐associated kinase‐M (IRAK‐M). Our previous studies have proved that IRAK‐M is induced by wear particles in macrophages from periprosthetic tissues. In this study, the IRAK‐M‐related mechanisms were further explored by lipopolysaccharide (LPS) and/or titanium (Ti) particles stimulations and small interfering RNAs (siRNAs). The protein level of IRAK‐M was studied using western blotting and tumor necrosis factor‐α (TNF‐α), and interleukin‐1β (IL‐1β) levels were measured using ELISA. Results showed that in RAW264.7 cells stimulated by LPS after Ti particle pre‐exposure, IRAK‐M was slightly changed, compared with LPS stimulation. And levels of TNF‐α and IL‐1β in cultures stimulated by LPS first after Ti particle pre‐exposure were lower than in the other two groups which were stimulated by LPS with or without Ti particles ( p < 0.001), whereas there were no statistic differences between the later two ( p > 0.05). The cytokines were lowest in Ti particles alone stimulation. After siRNAs silenced, IRAK‐M‐deficient cells exhibited increased expression of the cytokines in LPS stimulation after Ti particle pre‐exposure and when stimulated with Ti particles alone. Our findings suggest that debris‐induced IRAK‐M decreases foreign body reactions, but at the same time, the over‐expression of IRAK‐M may also be detrimental on local intrusion of PAMPs or bacteria, negatively regulates the LPS‐induced and TLRs‐mediated inflammation and results in immunosuppression in periprosthetic tissue, which may predispose to implant‐associated infections. © 2012 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 101A: 733–739, 2013.